“Influence of light intensity and Growth performance of acacia mangium : Seedlings in UMK Jeli Campus” - Nurhidayah Maisarah Zulfikar (2024)
Acacia mangium was a fast-growing tree species widely used in reforestation and agroforestry programs due to its adaptability and economic valued. This study examined the comparison of seedling growth rates understorey and the opened canopy environment of Acacia mangium and examined the light intensity of Acacia mangium seedling growth. Through the implementation of this method, the growth performance of Acacia mangium seedlings was carried out with correlation regression to distinguish between diameter, height, leaf and roots and based on shade or non-shade. In addition, this studied also examines the germination of seeds Acacia mangium. Overall result of germination tests was was 42% that lived as a result of the seed germination test conducted for 10 days. In addition, the temperature was also studied to saw the growth probability of Acacia mangium seedlings according to the temperature in Jeli, Kelantan. Apart from that, the growth of Acacia mangium was taken under shade and non-shade with a total of 70 seedlings that was shade had a total of 10 seedlings while non-shade had 60 seedlings of Acacia mangium. Although, this study was able to examine light as the main energy source for photosynthesis that allows seedlings to synthesize food from CO2 and water. Photosynthesis increases when there is sufficient light which accelerates the growth and development of seedlings. On the other hand, in low light conditions, seedlings may show morphological changes in leaves such as larger and thinner leaves to catch more light. Finally, this studied was useful in forest management for future planning.